Development of therapeutic supplement using roasted-cashew-nut to protect cerebral vasoconstriction injury triggered by mixture of petroleum hydrocarbons in the hypothalamus and hippocampus of rat model - J.K. Akintunde; V.O. Akomolafe; R.N. Ugbaja; A.M. Olude; A.D. Folayan (Toxicology Reports)
Petroleum-related activities have been a health global risk concern, particularly in the limbic disorders. The study aims to investigate the neuroprotection of roasted cashew nuts (RCN) on brain vasoconstriction injury induced by a mixture of petroleum hydrocarbons (MFPP). Seventy Male Wistar rats ranging 160 ± 10 g were randomized into seven groups. Group I was given distilled water. Group II was exposed to 0.2 ml MFPP. Group III, IV and V were exposed to 0.2 ml MFPP followed by treatment with 50 mg/kg atenolol, 10 % RCN and 20 % RCN, respectively. Group VI and VII were treated with 10 % RCN and 20 % RCN, respectively. The regimen period was 28 days. Cell pathological evaluation was done using hematoxylin and eosin staining and visualized under the microscope. Biochemical and molecular markers of brain vasoconstriction injury (BVI) were evaluated using spectrophotometer and RT-PCR analyzer, respectively. Student-T-test and one-way analysis of variance (ANOVA) were used to analyze the results. Sub-chronic exposure to MFPP induced BVI as evident in neuroinflammation and derangements in the histology of the hippocampus and hypothalamus coupled with momentous alterations in the neurons. Post treatment with RCN supplement remarkably modulated the effects by depleting the inflammatory mediators including HIF-1, p53 and MCP-1. Also, adenosinergic, purigenic and cholinergic of the hypothalamus and hippocampus were normalized by the supplement. It is pertinent to conclude that treatment with RCN inhibited BVI in rats via the NO-cAMP-PKA signaling pathway by reversing neuroinflammation, normalizing the purinergic and cholinergic neurotransmission in the hypothalamus and hippocampus, and stabilizing NO level coupled with brain histology improvement.